Effects of Differing Antecedent Hypoglycemia on Subsequent Counterregulation in Normal Humans - Davis, Stephen N; Shavers, Chris; Mosqueda-Garcia, Rogelio; Costa, Fernando (Diabetes (New York, N.Y.), 1997)
The aim of the study was to determine the effects of specific levels of antecedent hypoglycemia on subsequent autonomic, neuroendocrine, and metabolic counter-regulatory responses. Eight healthy, overnight-fasted male subjects were studied during 2-day protocols on four separate randomized occasions separated by at least 2 months. On day 1, insulin was infused at a rate of 9 pmol · kg−1 · min−1 and 2-h clamped euglycemia (plasma glucose 5.2 ± 0.2 mmol/l) or differing hypoglycemia (plasma glucose 3.9 ± 0.1, 3.3 ± 0.1, or 2.9 ± 0.1 mmol/l) was obtained during morning and afternoon. The next morning after an evening meal and 10-h overnight fast, each subject underwent a 2-h hyperin-sulinemic (9 pmol · kg−1 · min−1) hypoglycemic (2.9 ± 0.1 mmol/l) clamp study. Despite equivalent day 2 plasma glucose and insulin levels, differing levels of antecedent hypoglycemia produced specific blunting of subsequent counterregulatory responses. Day 1 hypoglycemia of 3.9 mmol/l resulted in significantly (P < 0.01) blunted epinephrine, muscle sympathetic nerve activity, and glucagon responses. Day 1 hypoglycemia of 3.3 mmol/l resulted in additional significant blunting (P < 0.01) of pancreatic polypeptide, norepinephrine, growth hormone, endogenous glucose production, and lipolytic responses. Deeper day 1 hypoglycemia of 2.9 mmol/l produced similar day 2 counterregulatory failure as day 1 hypoglycemia of 3.3 mmol/l. In summary, in healthy overnight-fasted men, mild antecedent hypoglycemia of 3.9 mmol/l significantly blunts sympathoadrenal and glucagon, but not other forms of neuroendocrine counterregulatory responses, to subsequent hypoglycemia. Antecedent hypoglycemia of 3.3 mmol/l resulted in additional significant blunting of all major neuroendocrine and metabolic responses to subsequent hypoglycemia. We conclude that in normal humans, there is a hierarchy of blunted counterregulatory responses that are determined by the depth of antecedent hypoglycemia.